The City of Culture: a Chronicle of Change Foretold - Lucrezia Lopez; María de los Ángeles Piñeiro Antelo; Miguel Pazos Otón (Il Capitale Culturale: Studies on the Value of Cultural Heritage, 2022)
At the beginning of the 1990s, one of the main architectural megaprojects in Spain took shape: the City of Culture, in Santiago de Compostela (Spain). Promoted and approved by the then president of the Galician government, Manuel Fraga, the main objective was to decongest the historic centre of Santiago de Compostela, the final destination of the Way of St. James and a World Heritage Site. Since then, it has been at the centre of numerous criticisms, among them many authors have denounced a “lack of planning”, since its peripheral location has been a problem towards achieving its initial objective. This proposal aims to analyse and reconstruct the evolution of uses and the urban imagery associated with the City of Culture, two aspects that have had to be modified in order for this space to survive in time. At the methodological level, planning documents have been reviewed and interviews were conducted in order to verify the political efforts.